Molecular confirmation of sarcocystis gigantean in a naturally infected sheep in Argentina: a case report. - Gual, Ignacio; Bartley, Paul; Katzer, Frank; Innes, Elisabeth; Canton, German Jose; Moore, Prando Dadin (Elsevier, 2019)
The work describes a case of Sarcocystis gigantea infection in a 3-years-old Corriedale ewe from Buenos Aires Province, Argentina. The ewe was found dead with a poor body condition. Pathological and molecular studies were carried out in order to try and confirm the causative agent of the infection. At necropsy, approx. 100 whitish elliptic (3–5 mm to 5–8 mm) macrocysts with a hard consistency were observed along the esophageal and pharyngeal muscular layers. Microscopically, the macrocysts consisted of an eosinophilic wall, internal septa originated from the eosinophilic wall and basophilic parasitic cells were located among the septa. The sarcocysts were identified molecularly through PCR amplification and sequencing of a short segment of the 18S rRNA gene. Sequence analysis of the amplified DNA demonstrated 100% identity to S. gigantea sequences previously published. To our knowledge this is the first molecular confirmation of S. gigantea infection in sheep in the Americas.